2015
DOI: 10.1016/j.chemer.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Petrology, geochemistry and tectonic significance of serpentinized ultramafic rocks from the South Arm of Sulawesi, Indonesia

Abstract: Serpentinized ultramafic rocks occur in two separate basement complexes in the South Arm of Sulawesi, the Bantimala and Barru Blocks. We present petrographic, mineral chemical and geochemical data for these rocks, and interpret them in terms of petrogenesis and tectonic setting.The rocks of both blocks show strong serpentinization of original anhydrous silicates. The Bantimala ultramafics consist mainly of peridotite (harzburgite and dunite) and clinopyroxenite, with lenses of podiform chromitite. Metamorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 30 publications
5
24
0
3
Order By: Relevance
“…According to the diagrams presented in Figure 10, we can argue that the Sulawesi chromitites formed in an SSZ from a single batch of magma with an initial high-Cr boninitic composition, which was undergoing differentiation in the deep mantle section and above to the Moho transition zone. This observation is in agreement with the conclusions reported by [34] that investigated serpentinized ultramafic rocks in the South Arm of Sulawesi. These authors, on the basis of whole-rock trace element analyses and spinel compositions, suggested that dunite, harzburgite and clinopyroxenite located in the Bantimala Block in the South Arm of Sulawesi are cumulates.…”
Section: Parental Melt and Chromite Composition: Tectonic Implicationssupporting
confidence: 83%
See 2 more Smart Citations
“…According to the diagrams presented in Figure 10, we can argue that the Sulawesi chromitites formed in an SSZ from a single batch of magma with an initial high-Cr boninitic composition, which was undergoing differentiation in the deep mantle section and above to the Moho transition zone. This observation is in agreement with the conclusions reported by [34] that investigated serpentinized ultramafic rocks in the South Arm of Sulawesi. These authors, on the basis of whole-rock trace element analyses and spinel compositions, suggested that dunite, harzburgite and clinopyroxenite located in the Bantimala Block in the South Arm of Sulawesi are cumulates.…”
Section: Parental Melt and Chromite Composition: Tectonic Implicationssupporting
confidence: 83%
“…However, as documented by [37], low-Ca content is not unique to mantle olivine. Since the presence of cumulate ultramafics rocks has been reported in the Bantimala Block located the in the South Arm of Sulawesi [34], we cannot exclude the possibility that the Alekale and Kalamasse chromitites formed above the Moho-transition zone.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…As Sc is a compatible element, mafic and ultramafic rocks generally have higher Sc contents. Sc is incorporated into pyroxene (or amphibole), but is rarely contained in olivine (Leeman and Scheidegger, 1977 (Onuma et al, 1968;Sanematsu et al, 2014;Maulana et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the formation of ferrian-chromite and chromian magnetite alteration rims around the Al-spinels, Cr-spinels and magnesiochromites is assigned to secondary processes that typically occur during serpentinisation (Khedr and Arai, 2011;Singh et al, 2013;Banerjee et al, 2015;Maulana et al, 2015). Notable Mn-erichments in the ferrian chromite zones involve interaction of hydrothermal fluids that were likely rich in Mn, similarly to other ophiolite complexes (e.g., Gahlan and Arai, 2007).…”
Section: Discussionmentioning
confidence: 99%